Managing The Environment In Making Children Friendly Schools In SMA 45, Jakarta - Mohammad Iqbal; Anoesyirwan Moeins; Meita Pragiwani (BPJP - STEI, 2020)
Abstract—This study aims to determine environmental management in creating Child Friendly Schools in SMA 45 Jakarta. This research method is quantitative descriptive method. The object of this research is SMA 45 Jakarta, which is located at Jln. Perintis Kemerdekaan Kelapa Gading - North Jakarta. While the subjects or respondents (informants) selected in this study were teachers and parents and students of SMA Negeri 45 who had direct links to the topic, because this research was in the form of case studies, so the related parties were used as respondents. While the data source in this study is the result of in-depth observation activities to get a real picture of the actual situation that occurred at SMA Negeri 45 Jakarta.The results of this study indicate that environmental management to create a Child Friendly School in SMA 45 Jakarta has been in accordance with the components of a child friendly school well, this can be seen from the average value of the statement items on the child friendly school indicators that indicate respondents' answers tend with answers agree and strongly agree so that it has a very good interpretation.